Energy management and performance evaluation of grid connected PV-battery hybrid system with inherent control scheme - Guichi, Amar; Talha, Abdelaziz; Berkouk, El Madjid; Mekhilef, Saad (Elsevier, 2018)
To decrease the payback time of the photovoltaic (PV) system and make it financially attractive, we propose a Photovoltaic Customer Grid Supply System (PCGSS) with bi-directional power flow, so the surplus energy fully or partially is delivered of the grid, following its needs, while, for critical operating conditions, the grid supplies the loads directly. For this purpose, a new management algorithm is proposed to optimize the generated power and allows the system to act as a distributed source inside the utility grid. Two scenarios are considered; in the first, the grid absorbs all the power delivered by the distributed system, while in the second, the power is injected to the grid based on the its requirements. Furthermore, to meet the proposed objectives, the PV system is strictly sized to supply only the high priority loads, in addition, the system has to work at the Maximum Power Point (MPP) or at the Limited Power Point (LPP) modes to meet the management algorithm requests. To reach the LPP, a modified Perturbation and Observation (P&O) algorithm is used. Meanwhile, to sustain the functionality of the system and to assure the continues supply of energy, a battery system has been integrated with the PV system.